2021
DOI: 10.1097/hs9.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Digital PCR Improves IG-/TR-based MRD Risk Definition in Childhood B-cell Precursor Acute Lymphoblastic Leukemia

Abstract: Minimal residual disease (MRD) is the most powerful prognostic factor in pediatric acute lymphoblastic leukemia (ALL). Real-time quantitative polymerase chain reaction (RQ-PCR) represents the gold standard for molecular MRD assessment and risk-based stratification of front-line treatment. In the protocols of the Italian Association of Pediatric Hematology and Oncology (AIEOP) and the Berlin-Frankfurth-Munschen (BFM) group AIEOP-BFM ALL2009 and ALL2017, B-lineage ALL patients with high RQ-PCR-MRD at day+33 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Moreover, Fluidigm digital PCR assay has been used in the ENESTnext (NCT01227577) study, confirming that ddPCR is more sensitive than RT-qPCR in patients with confirmed MR4.5, since about 40% of analyzed samples had a detectable BCR-ABL1 [26]. Our data also corroborated results previously obtained by Della Starza et al in pediatric acute lymphoblastic leukemia, where they identify ddPCR as more accurate than RT-qPCR in the measurement of MRD, particularly in the advanced follow-up [27]. Moreover, we showed no differences between duplicate or quadruplicate analysis, even for the lowest levels of disease.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, Fluidigm digital PCR assay has been used in the ENESTnext (NCT01227577) study, confirming that ddPCR is more sensitive than RT-qPCR in patients with confirmed MR4.5, since about 40% of analyzed samples had a detectable BCR-ABL1 [26]. Our data also corroborated results previously obtained by Della Starza et al in pediatric acute lymphoblastic leukemia, where they identify ddPCR as more accurate than RT-qPCR in the measurement of MRD, particularly in the advanced follow-up [27]. Moreover, we showed no differences between duplicate or quadruplicate analysis, even for the lowest levels of disease.…”
Section: Discussionsupporting
confidence: 89%
“…[ 68 ]. Trying to address this issue, Dr. Della Starza and coworkers proposed ddPCR as an alternative method for MRD monitoring [ 11 , 69 ] in samples from patients enrolled in the GIMEMA LAL1308 and in the AIEOP-BFM ALL 2000 trials, finding a concordance rate of 70% between QT-PCR and ddPCR. The greater accuracy of ddPCR allowed to quantitate samples defined as PNQ by QT-PCR in a quarter of cases.…”
Section: Ddpcr Applications In Hematologymentioning
confidence: 99%
“…Although NGS and ddPCR have not yet been fully implemented into routine practice, there are hints that both methods possess appreciable advantages over RQ-PCR. Particularly samples which are positive below the quantitative range (pos < QR) of RQ-PCR can often be assessed more confidently: thanks to the more specific readout of NGS, false-positive RQ-PCR results which might occur due to the nonspecific amplification can be reliably distinguished from truly positive samples [ 101 ]; ddPCR is able to provide an accurate MRD quantification in 20–45% of pos < QR samples thanks to its absolute quantification without the need of a standard curve [ 102 , 103 , 104 , 105 ]. Another frequently mentioned advantage of the modern methods is the improved sensitivity.…”
Section: Minimal Residual Diseasementioning
confidence: 99%